Women College Students Situation During Pandemic Time: How’s Their Access to the Future? - Delavin, Elreen Aguilar; Barazon Jr, Leviticus M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
The COVID-19 pandemic is a unique and rare occurrence in the whole world. It compelled colleges to close their doors and transition entirely to distance learning. It posed many challenges in the academe with the abrupt change in the educational landscape. Hence, the study was conceived on determining answers in a 15-question closed-question from a Plan International survey in which women college students were asked about their understanding of the COVID-19 pandemic and its effects on their life and access to education, welfare, economic security, livelihoods, and access to technology. It was found out that the respondents knew little about COVID- 19, it made a major change in their lives which led to huge effect to their access to their future plans. However, based from their responses on the qualitative side of the study they still have hopes and aspiration despite the pandemic situation. As a result, its impact on female college students, who confront special vulnerabilities, must be recognized, and their experiences and perspectives must be incorporated in the institution's COVID-19 pandemic preparedness processes.